The human RNA helicase DHX37 is required for release of the U3 snoRNP from pre-ribosomal particles - Choudhury, Priyanka (RNA Biol, 2018)
Ribosome synthesis is an essential cellular process, and perturbation of human ribosome production is linked to cancer and genetic diseases termed ribosomopathies. During their assembly, pre-ribosomal particles undergo numerous structural rearrangements, which establish the architecture present in mature complexes and serve as key checkpoints, ensuring the fidelity of ribosome biogenesis. RNA helicases are essential mediators of such remodelling events and here, we demonstrate that the DEAH-box RNA helicase DHX37 is required for maturation of the small ribosomal subunit in human cells. Our data reveal that the presence of DHX37 in early pre-ribosomal particles is monitored by a quality control pathway and that failure to recruit DHX37 leads to pre-rRNA degradation. Using an in vivo crosslinking approach, we show that DHX37 binds directly to the U3 small nucleolar RNA (snoRNA) and demonstrate that the catalytic activity of the helicase is required for dissociation of the U3 snoRNA from pre-ribosomal complexes. This is an important event during ribosome assembly as it enables formation of the central pseudoknot structure of the small ribosomal subunit. We identify UTP14A as a direct interaction partner of DHX37 and our data suggest that UTP14A can act as a cofactor that stimulates the activity of the helicase in the context of U3 snoRNA release.